2013
DOI: 10.3233/thc-130720
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of using C-reactive protein for point-of-care testing

Abstract: BACKGROUND: C-reactive protein (CRP) point-of-care testing (POCT) can be a valuable tool for decision making in primary care. Very few studies have illustrated the utilization of CRP POCT. OBJECTIVE: To conduct a systematic review on the use of CRP POCT in primary care settings and to examine its feasibility and acceptability in an outpatient primary care setting. METHODS: The search was conducted via PubMed. Final articles in the systematic review met inclusion and exclusion criteria. For the feasibility and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
(50 reference statements)
0
12
0
Order By: Relevance
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
“…After full-text evaluation, 152 publications were relevant for POCT. After excluding 34 publications [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 ] ( Supplementary Materials ), 13 studies [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ] reported across 22 publications [ 61 , 62 , 63 …”
Section: Resultsmentioning
confidence: 99%
“…CRP marker could be a useful predictive tool in assisting diagnosis of probable bacterial aetiology causing febrile infections. Analysis using CRP rapid diagnostic test have shown to be cost effective and more easily accessible than blood culturing for prompt and appropriate antimicrobial treatment among paediatrics in countries with limited microbiology facilities [41, 42]. Over half of patients in the study had fever lasting 24 to 48 hours.…”
Section: Discussionmentioning
confidence: 99%
“…antibacterial therapy to levels that are indistinguishable from healthy controls. Interesting, the increased HLA-G in a subgroup of patients with CF was inversely related to levels of CRP, a biomarker of systemic inflammation [26]. An impact of the role of HLA-G molecules in immune-regulation, for example in the creation of a tolerogenic environment at the maternal-fetal interface [15] and in transplanted patients [16,30], has been already suggested.…”
Section: Discussionmentioning
confidence: 96%
“…The i.v. treatment improved FEV1 values (≥ 5% positive increase of FEV1, Table 2) while the acute phase reaction pentraxin C-reactive protein (CRP), an inflammation-related biomarker [26], was drastically reduced ( Table 2). Interesting, variations of CRP plasma levels were inversely correlated to sHLA-G in 30% of CF patients (Spearman Correlation r=-0.307; P=0.032), while no significant correlations were observed with FEV1 values and the outcome of microbial infections (data not shown).…”
Section: Intravenous Antibiotic Therapy Influences Hla-g Expression Imentioning
confidence: 99%